2022
DOI: 10.1016/j.redox.2021.102212
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6 protects irradiated cells from oxidative stress and shapes their senescence-associated cytokine landscape

Abstract: Cellular senescence is a complex stress response defined as an essentially irreversible cell cycle arrest mediated by the inhibition of cell cycle-specific cyclin dependent kinases. The imbalance in redox homeostasis and oxidative stress have been repeatedly observed as one of the hallmarks of the senescent phenotype. However, a large-scale study investigating protein oxidation and redox signaling in senescent cells in vitro has been lacking. Here we applied a proteome-wide analysis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…The age-dependent accumulation of senescent cells is caused by age-related attenuated efficiency of the immune system [16] and their higher resistance both to extrinsic and intrinsic pro-apoptotic stimuli [16][17][18], including oxidative stress [19]. While the mechanisms driving senescence are well studied, understanding the mechanisms endowing these cells with increased survival capacity is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The age-dependent accumulation of senescent cells is caused by age-related attenuated efficiency of the immune system [16] and their higher resistance both to extrinsic and intrinsic pro-apoptotic stimuli [16][17][18], including oxidative stress [19]. While the mechanisms driving senescence are well studied, understanding the mechanisms endowing these cells with increased survival capacity is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple types of stimulations, such as chemotherapy and radiation, can induce senescent cells to secrete high levels of interleukins, inflammatory cytokines, proteases, and growth factors, which are collectively referred to as senescence-associated secretory phenotype (SASP) [ 104 ]. A recent study using ionizing radiation-induced senescence (IRIS) cell model demonstrated that PRX6 is an important contributor to protection against oxidative-stress-induced cell death in senescent cells by attenuation of senescence-associated proinflammatory cytokine IL-6 secretion [ 105 ]. SASP can either promote or inhibit cancer, depending on the SASP composition.…”
Section: Prx6 and Senescence-associated Secretory Phenotypementioning
confidence: 99%
“…In addition, IL-6 is the most prominent cytokine of the SASP. PRX6 silencing decreased expression of extracellular matrix proteins including IL6 in IRIS hTERT-RPE-1 cells [ 105 ].…”
Section: Prx6 and Senescence-associated Secretory Phenotypementioning
confidence: 99%
“…Maintaining cellular protein homeostasis, or proteostasis, requires the well-coordinated control of protein synthesis, folding, conformational integrity, and ultimately degradation. Proteostasis activities coordinate these diverse processes across the lifespan of all organisms [125]. The proteostatic regulatory network ensures that cells have the proteins they need, while minimizing misfolding or aggregation events that are hallmarks of aging-associated proteinopathies, such as Alzheimer's, Parkinson's, and Huntington's disease [126][127][128][129][130].…”
Section: Proteostasis/fibrosismentioning
confidence: 99%